2021
DOI: 10.3390/robotics10030100
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Control of Hexapod Robots: A Survey

Abstract: The static stability of hexapods motivates their design for tasks in which stable locomotion is required, such as navigation across complex environments. This task is of high interest due to the possibility of replacing human beings in exploration, surveillance and rescue missions. For this application, the control system must adapt the actuation of the limbs according to their surroundings to ensure that the hexapod does not tumble during locomotion. The most traditional approach considers their limbs as robo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Contact forces can be used to generate adaptive gaits [37][38][39]. Dynamic control can achieve desired task accelerations [40].…”
Section: Introductionmentioning
confidence: 99%
“…Contact forces can be used to generate adaptive gaits [37][38][39]. Dynamic control can achieve desired task accelerations [40].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of our glove is to relate motions of a common hexapod leg to finger motions. A common robot leg design has three joints ( Graf et al, 2019 , 2021 ; Wooden et al, 2010 ; Boston Dynamics, 2022 ; Michael, 2012 ; Hwangbo et al, 2019 ; Darling, 2015 ; Sartoretti et al, 2018 ; Coelho et al, 2021 ), as shown in Figure 3 : a hip joint with vertical axis of rotation, a knee joint, and an ankle joint with parallel axes of rotation. Just like one robot leg has three joints, there are three joints on one finger: the metacarpophalangeal joint (MCP), the proximal interphalangeal joint (PIP) and the distal interphalangeal joint (DIP) ( Jones and Lederman, 2006 ; Palastanga and Soames, 2011 ; Wheatland et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there are currently few successful cases of rescue robots performing rescue tasks. Mobile robots are mainly divided into wheeled, legged, tracked, and hybrid types [ 1 , 2 ]. Compared with wheeled robots, legged-wheeled robots have better passability, and compared with legged robots, they have higher stability, combining all the advantages of wheeled and legged robots [ 3 ].…”
Section: Introductionmentioning
confidence: 99%